Frequent somatic mosaicism in T lymphocyte subsets in individuals with and without multiple sclerosis - Van Horebeek, Lies; Dedoncker, Nina; Dubois, Bénédicte; Goris, An (Frontiers in Immunology, 2022)
Background: Somatic variants are variations in an individual’s genome acquired after the zygotic stadium and result from mitotic errors or not (fully) repaired DNA damage. Objectives: To investigate whether somatic mosaicism in T lymphocyte subsets is enriched early in multiple sclerosis (MS). Methods: We identified somatic variants with variant allele fractions ≥1% across the whole exome in CD4+ and CD8+ T lymphocytes of 21 treatment-naïve MS patients with <5 years disease duration and 16 partially age-matched healthy controls. We investigated the known somatic STAT3 variant p.Y640F in peripheral blood in a larger cohort of 446 MS patients and 259 controls. Results: All subjects carried 1-142 variants in CD4+ or CD8+ T lymphocytes. Variants were more common, more abundant and increased with age in CD8+ T lymphocytes. Somatic variants were common in genes DNMT3A and especially STAT3. Overall, the presence or abundance of somatic variants, including the STAT3 p.Y640F variant, did not differ between MS patients and controls. Conclusions: Somatic variation in T lymphocyte subsets is wide-spread, in both control individuals and MS patients. Somatic mosaicism in T subsets is not enriched in early MS and thus unlikely to contribute to MS risk, but future research needs to address whether a subset of variants influences disease susceptibility.